Health risk factors and self-rated health among job-seekers - Tobschall Stefanie; Gaertner Beate; Freyer-Adam Jennis; John Ulrich (BMC, 2011)
Abstract Background To determine a) proportions of behavior related health risk factors among job-seekers and b) to what extend these are related to self-rated health. Methods Over 12 months, job-seekers were recruited at three job-agencies in northeastern Germany. Among all individuals eligible for study inclusion, 7,906 (79.8%) provided information on smoking, risky drinking, overweight/obesity (body mass index), fruit and vegetable intake, physical inactivity, illicit drug use, and self-rated health. Proportions and 95% confidence intervals stratified by gender, age and duration of unemployment were calculated. Multivariate logistic regression analyses predicting self-rated health were conducted. Results The proportions of each health-risk factor were high, and 52.4% of the sample (53.4% male, 33.5 years mean age) had 3 or more health risk factors. Mostly, the proportions were particularly high among men and long-term unemployed individuals; e.g. 84.8% of the 18-24 year old long-term unemployed men were current smokers. Proportions of substance use related health risk factors were highest among the 18-24 year olds (e.g. risky drinking 28.7%), and proportions of health risk factors related to nutrition and physical inactivity were highest among the 40-64 year olds (e.g. overweight/obesity 65.4%). Depending on gender, all health risk factors and having 3 or more health risk factors were associated with lower self-rated health; odd ratios ranged between 1.2 for smoking (95% CI: 1.0-1.3) and 1.7 for overweight and physical inactivity (95% CI: 1.5-1.9). Conclusions Prevention efforts to reduce health risk factors and to increase health among job-seekers are needed, and job agencies appear a feasible setting for their implementation.